Effect of pH variations in a cycling model on the properties of restorative materials - Silva, K. G.; Pedrini, Denise [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Cannon, M. (Operative Dentistry Inc, 2007)
This study evaluated the effect of cycling various pH demineralizing solutions on the surface hardness, fluoride release and surface properties of restorative materials (Ketac-Fil Plus, Vitremer, Fuji II LC, Freedom and Fluorofil). Thirty specimens of each material were made and the surface hardness measured. The specimens were randomized into five groups according to the pH (4.3; 4.6; 5.0; 5.5 and 6.2) of the demineralizing solution. The specimens were submitted to pH-cycling for 15 days. The specimens remained in the demineralizing solution for six hours and in the remineralizing solution for 18 hours. Then, the surface hardness (SH) was remeasured and the surface properties were assessed. Fluoride release was determined daily. Data from SH and the percentage of alteration in surface hardness were analyzed by analysis of variance (p < 0.05); the Kruskal-Wallis test was performed for the fluoride release results. When hardness was compared, the variation in pH led to a positive correlation for glass ionomer cements and a negative correlation for fluoride release. For polyacid-modified resin composites, a negative correlation was found with regards to fluoride release; no significant correlation was observed for hardness. Surface properties were influenced: an acidic pH led to a greater alteration, except for polyacid-modified resin composites. The pH of the demineralizing solution influenced fluoride release from the tested materials. The pH variation altered hardness and surface properties of glass ionomer cements but did not influence polyacid-modified resin composites.